(untitled) (Nóema, 2023)
What happens to thought when teaching in a university institution? Starting from the teaching experience and some writings of Roland Barthes, in particular Lecture, inaugural speech at the Collège de France, the essay questions the seminar, defined as "an institution drawn on the utopian model", which accompanied, from seventies onwards, the writing and courses of the French semiologist.